The Effect of Attitude and Intention on Adoption of Women and Child Protection Application Tangerang City - Sandra Oktaviani; Rini Laili Prihatini; Muhtadi; Maria Ulfah; Wati Nilamsari (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2026)
The expansion of digital public services reflects changing communication practices aimed at increasing participation and social justice. Grounded in Rogers’ Diffusion of Innovations and attitude–intention communication frameworks, this study examines how attitudes and intentions influence the adoption of the Silacakperak application for reporting violence against women and children. It hypothesizes that attitude positively affects intention and innovation adoption, with intention acting as a mediator. A quantitative explanatory design was applied using a survey of 384 respondents in Tangerang City. Data were collected through structured questionnaires and analyzed using statistical models to test direct and mediating relationships among attitude, intention, and innovation adoption. The findings show that attitude significantly influences intention and innovation adoption, while intention also has a significant positive effect on adoption and mediates the attitude–adoption relationship. These results are consistent with prior communication studies and empirically support diffusion of innovations theory in the context of digital public service communication. Attitude and intention are central communicative factors in the adoption of digital reporting applications, underscoring the importance of persuasive communication strategies in technology-based public services.